Radikal Prima Bi-Ideal Dalam Semiring Ternari - Ratna Sari Widiastuti (Jurnal Matematika, 2019)
A ternary semiring is an additive commutative semigroup with a ternary multiplication which satisfying some condition. This paper will be discuss about prime bi-ideal radikal in semiring ternary with definition and some theorem. If B is a bi-ideal in semiring ternary T, then radical prime bi-ideal of B in semiring ternary T is an intersection of all prime bi-ideal in semiring ternary T which containing B.